Alectinib-Loaded Chitosan–Alginate Nanoparticles: A Novel Synthesis Method with In Vitro and In Vivo Evaluations - Tha’er Ata; Israa Al-Ani; Nida Karameh; Mahmood R. Atta; Wael Abu Dayyih (Pharmaceutics)
Background/Objectives: Non-small cell lung cancer (NSCLC) constitutes over 84% of all lung cancer cases and is a leading cause of cancer-related mortality globally. Alectinib, a second-generation anaplastic lymphoma kinase (ALK) inhibitor, is effective in ALK-positive NSCLC; however, its clinical potential is hampered by poor aqueous solubility and limited oral bioavailability. This study aimed to develop Alectinib-loaded chitosan–alginate nanoparticles (ACANPs) to enhance its solubility, oral bioavailability, and therapeutic efficacy. Methods: ACANPs were synthesized using a novel combined solid/oil/water (s/o/w) emulsification technique with ionotropic gelation. Characterization was performed using Fourier-transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), dynamic light scattering (DLS), and zeta potential measurements. A validated high-performance liquid chromatography (HPLC) method quantified the Alectinib. In vitro drug release studies compared free Alectinib with ACANPs. Cytotoxicity against NSCLC cell lines (A549 and H460) was assessed using MTT assays. Pharmacokinetic parameters were evaluated in rats using LC–MS/MS. Results: ACANPs showed a high encapsulation efficiency (~97%), an average particle size of 161 nm, and a positive zeta potential of +21 mV. In vitro release studies revealed a threefold increase in drug release from ACANPs over 48 h compared to free Alectinib. Cytotoxicity assays demonstrated significantly reduced IC50 values for ACANPs. Pharmacokinetic analyses showed an enhanced maximum plasma concentration (Cmax) and area under the curve (AUC), indicating a 78% increase in oral bioavailability. Conclusions: ACANPs substantially improved the solubility, cytotoxic efficacy, and oral bioavailability of Alectinib, suggesting their potential as a promising nanocarrier system for enhancing NSCLC treatment outcomes.